(untitled) (Web of Teachers: Inderscience Research, 2024)
This article reflects on the priority issues of improving the activities of music education circle training, as well as on the development and enrichment of the ability to musical creativity, the formation of music perception skills, their implementation of amateur activities on a consistent system,as well as on modern teaching trends.